2007
DOI: 10.1016/j.prostaglandins.2007.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclo-oxygenase-2 in macrophages associated with cutaneous melanoma at different stages of progression

Abstract: The biological significance of the almost constant presence of macrophages in the tumoral microenvironment is an issue debated by several authors. The major difficulty in understanding the role played by tumor-associated macrophages (TAMs) in tumor progression is due to the contrasting effects of TAMs found in different studies. In addition, there is a limited information on which of the many biological activities expressed by TAMs are critical in inducing stimulatory or inhibitory effect on tumor growth. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 32 publications
2
37
0
3
Order By: Relevance
“…By osteopontin signalling, COX-2 expression is upregulated in macrophages, inducing increased MMP-9 secretion to promote angiogenesis and invasiveness of melanocytic tumours [52]. An in-vitro study has reported that only upon contact with melanoma cells could macrophages express COX-2 [53]. Furthermore, macrophages seem to be capable of inducing COX-2 expression in breast carcinomas, amplifying IL-1β signalling through the MAPK pathway, which is involved in tumour progression [54].…”
Section: Discussionmentioning
confidence: 99%
“…By osteopontin signalling, COX-2 expression is upregulated in macrophages, inducing increased MMP-9 secretion to promote angiogenesis and invasiveness of melanocytic tumours [52]. An in-vitro study has reported that only upon contact with melanoma cells could macrophages express COX-2 [53]. Furthermore, macrophages seem to be capable of inducing COX-2 expression in breast carcinomas, amplifying IL-1β signalling through the MAPK pathway, which is involved in tumour progression [54].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have demonstrated the wide range of effects for COX-2 product PGE2 in carcinogenesis and tumor development, including inducing angiogenesis, promoting cellular proliferation, inhibiting cell apoptosis, stimulating tumor invasion, and so on [28]. In melanoma, COX-2 is associated with tumor progression [29][31].Similarly, inducible NO synthases (iNOS) and its product NO have also shown overexpression in different types of cancer, including melanoma. iNOS is overexpressed in most cultured melanoma cells and in human melanoma samples [32], [33].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of macrophages in primary lesions was revealed in cutaneous melanomas (19), uveal melanomas (20,21) and sinonasal melanomas (22). In the case of cutaneous lesions, they are predominantly located in the primary foci, and to a lesser extent in metastatic foci (19).…”
Section: Macrophages In Skin Melanomasmentioning
confidence: 98%
“…In the case of cutaneous lesions, they are predominantly located in the primary foci, and to a lesser extent in metastatic foci (19). Elevated numbers of macrophages within a melanoma is markedly associated with poor prognosis (23).…”
Section: Macrophages In Skin Melanomasmentioning
confidence: 99%
See 1 more Smart Citation